Molar distalizer with nickel-titanium pistons. A case presentation. (Colombia Medica, 2007)
Various devices have been used to distalize upper molars on class II malocclusion patients. It has been noted that most of those devices tend to incline and rotate first molars’ crowns, because of the force applied on them. This presentation introduces a fixed device that is able to move distally upper molars with reduced rotation or distal inclination. Therefore, the use of extra-oral forces would be minimized. Constant low intensity forces applied by the nickel titanium’s open spring piston optimizes movement and decreases treatment time. Another advantage of this specific device is the fact, that it is bonded, so patient’s high degree of cooperation is no a requirement for upper molars distalization treatments.